Treatment of Cotton by β-Cyclodextrin/Triclosan Inclusion Complex and Factors Affecting Antimicrobial Properties - Novikov, Mikhail; Thong, Kwai Lin; Zazali, Nur Izzurianna Mohd; Hamid, Sharifah Bee Abd (Springer Verlag, 2018)
The efficacy of antimicrobial treatment of cotton fabrics depends on various parameters of the coating process, such as the chemical nature and concentration of the antimicrobial agent, the composition of the crosslinking formulation, and the curing temperature. The inclusion complex of triclosan with β-cyclodextrin (βCD) was synthesized and characterized by FTIR, XRD, NMR, Raman, SEM, and TGA. The minimum inhibitory concentration and minimum bactericidal concentration of the complex against Klebsiella pneumoniae and Staphylococcus aureus were compared to those of its precursor. A multifactorial study included an evaluation of the effects of triclosan complexation with β-cyclodextrin, a comparison between the glyoxal and tetracarboxylic acid as crosslinkers, an investigation of the effect of crosslinker and catalyst concentrations, and a comparison of curing at 120°C and 180°C. The cotton was characterized by FTIR-ATR, the micrographs of treated samples were obtained by SEM and the weight add-on was calculated. The bactericidal properties were determined according to AATCC-147. The correlation between the coating process parameters and the antimicrobial efficacy was determined. The optimal combination leading to the highest weight add-on and the antimicrobial coating that was most durable to multiple detergent washes at an elevated temperature was the use of complexed triclosan grafted onto the cotton in the presence of tetracarboxylic acid, followed by curing at 180°C. The curing temperatures were 120°C (P=0.002) and 180°C (P=0.008), catalysts were 1 % and 2 % aluminium sulfate and sodium hypophosphite (P<0.001), and the crosslinkers were 5 % and 10 % glyoxal and butanetetracarboxylic acid (P<0.001); these parameters significantly enhanced the antimicrobial properties of the treated fabrics. The study showed that βCD did not have antimicrobial activity, while the βCD/triclosan-treated textile exhibited potential antimicrobial properties. Overall, the bactericidal activity of fabrics can be enhanced by using βCD/triclosan with 10 % butanetetracarboxylic acid as a cross-linker and 5 % sodium hypophosphite as a catalyst at a curing temperature of 180°C.